A study on three mineral pieces of the Natural History Museum at the UNMSM by using physical techniques - Cerón, María (2020)
By using analytical physical techniques, we studied three mineral pieces belonging to the Natural History Museum at the San Marcos National University. Our aim is to get details concerning their elemental and structural composition. Specically, we have utilized techniques such as energy dispersive X-ray fluorescence, X-ray difractometry, and Mössbauer spectroscopy, light optical microscopy and scanning electron microscopy. We used this last one along with energy dispersive X-ray spectroscopy. The obtained results indicate that samples MHN-09 and MHN-11 are impactites. This means that there was a meteorite impact on Huánuco a long time ago. Likewise, we found that sample MHN-03 is magnetic in accordance with the results obtained by energy dispersive X-ray fluorescence and Mössbauer spectroscopy.